Evolution of Crushing Surface of Ta-d Pumice in Triaxial Compression Tests - Sato, Itsuki; Kuwano, Reiko; Otsubo, Masahide; Mohri, Atsushi (Himpunan Ahli Teknik Tanah Indonesia, 2024)
Crushable porous granular materials like volcanic pumice, distributed worldwide, cause various engineering problems, including slope hazards. These materials are often classified as problematic soils due to their complex mechanical properties, which arise from high compressibility and changes in grain size due to particle crushing. Consequently, their behaviour is typically discussed on a case-by-case basis, and a systematic understanding has yet to be established. This study aims to elucidate the relationship between the mechanical properties and particle crushing of porous granular materials through a series of tests on natural volcanic pumice. The intra-particle void ratio was measured alongside isotropic consolidation and CD/CU triaxial compression tests, with particle crushing assessed before and after the experiments. The results indicate that the intra-particle void ratio correlates with particle size, with larger particles generally having higher porosity. Additionally, the mechanical behaviour of these materials shows high compressibility, and their stress paths resemble those obtained from undrained triaxial tests on loose sand, ultimately reaching the critical state. The relationship between the amount of particle crushing and mean effective stress at the end of the tests can be represented by a single curve for isotropic consolidation tests, CD, and CU triaxial tests, respectively. The amount of crushing generally increases with the progression of axial strain during the compression process, and in CU tests, when reaching the critical state, no further increase in crushing occurs with increased axial strain. Furthermore, critical state and isotropic consolidation state of each material can be represented on its own unique surface, each referred to as a